Myocardial iron content and mitochondrial function in human heart failure: a direct tissue analysis - Melenovský, Vojtěch; Petrak, Jiri; Mráček, Tomáš; Beneš, Jan; Borlaug, Barry A; Nuskova, Hana; Pluhacek, Tomas; Špatenka, Jaroslav; Kovalcikova, Jana; Drahota, Zdeněk; Kautzner, Josef; Pirk, Jan; et al. (European journal of heart failure, 2017)
AIMS: Iron replacement improves clinical status in iron-deficient patients with heart failure (HF), but the pathophysiology is poorly understood. Iron is essential not only for erythropoiesis, but also for cellular bioenergetics. The impact of myocardial iron deficiency (MID) on mitochondrial function, measured directly in the failing human heart, is unknown. METHODS AND RESULTS: Left ventricular samples were obtained from 91 consecutive HF patients undergoing transplantation and 38 HF-free organ donors (controls). Total myocardial iron content, mitochondrial respiration, citric acid cycle and respiratory chain enzyme activities, respiratory chain components (complex I-V), and protein content of reactive oxygen species (ROS)-protective enzymes were measured in tissue homogenates to quantify mitochondrial function. Myocardial iron content was lower in HF compared with controls (156 ± 41 vs. 200 ± 38 µg·g-1 dry weight, P < 0.001), independently of anaemia. MID (the lowest iron tercile in HF) was associated with more extensive coronary disease and less beta-blocker usage compared with non-MID HF patients. Compared with controls, HF patients displayed reduced myocardial oxygen2 respiration and reduced activity of all examined mitochondrial enzymes (all P < 0.001). MID in HF was associated with preserved activity of respiratory chain enzymes but reduced activity of aconitase and citrate synthase (by -26% and -15%, P < 0.05) and reduced expression of catalase, glutathione peroxidase, and superoxide dismutase 2. CONCLUSION: Myocardial iron content is decreased and mitochondrial functions are impaired in advanced HF. MID in HF is associated with diminished citric acid cycle enzyme activities and decreased ROS-protecting enzymes. MID may contribute to altered myocardial substrate use and to worsening of mitochondrial dysfunction that exists in HF.
Keywords: Female; lidé středního věku; železo; mužské pohlaví; Case-Control Studies; Heart Transplantation; Humans; dospělí; myokard; Mitochondria, Heart; srdeční selhání; lidé; Middle Aged; srdeční mitochondrie; senioři; Myocardium; ženské pohlaví; studie případů a kontrol; Iron; Aged; Heart Failure; Adult; Male; transplantace srdce